2020
DOI: 10.1002/bem.22264
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Changes in Magnetic Variations and Light–Dark Cycle on Life‐History Traits of Daphnia magna

Abstract: Day–night cycle is the main zeitgeber (time giver) for biological circadian rhythms. Recently, it was suggested that natural diurnal geomagnetic variation may also be utilized by organisms for the synchronization of these rhythms. In this study, life‐history traits in Daphnia magna were evaluated after short‐term and multigenerational exposure to 16 h day/8 h night cycle, 32 h day/16 h night cycle, diurnal geomagnetic variation of 24 h, simulated magnetic variation of 48 h, and combinations of these conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Life-history traits, general amylolytic activity, general proteolytic activity, and sucrase activity were utilized to evaluate the biological effects of magnetic fields. Previously, it was shown that these characteristics are sensitive to magnetic influences [ 27 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Life-history traits, general amylolytic activity, general proteolytic activity, and sucrase activity were utilized to evaluate the biological effects of magnetic fields. Previously, it was shown that these characteristics are sensitive to magnetic influences [ 27 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diurnal geomagnetic variation is suggested to act as a potential circadian zeitgeber via cytochromes possibly being able to perceive magnetic fields through radical pair reactions [12,13]. Though indirect evidence supports this theory [14,15,16,17,18,19,20], no direct experimentation has been carried out studying the entrainment of circadian rhythms to slow magnetic fluctuations. The issue of whether slow changes in the magnetic field affect circadian oscillators remains open.…”
Section: Introductionmentioning
confidence: 99%